Locking condylar plate: best device to treat supracondylar fractures of the femur - Pallewad, Irwant V.; Kagne, Vijay B.; Upadhye, Jayshree J. (International Journal of Research in Orthopaedics, 2019)
Background: Supracondylar fractures of the femur in adults account for only 7% of all femoral fractures. However, these fractures present with numerous complications. The purpose of this study was to assess the outcome of locking condylar plate in supracondylar fractures of femur in adults. Methods: This study was based on 25 patients of supracondylar fracture of the femur treated with locking condylar plate at Srinivas Institute of Medical Sciences and Research Centre, Mukka, Suratkal, Mangalore. The patients were followed up for 1 year. Results: In present study, 84% fractures were sustained due to road traffic accidents. In 23 (92%) patients, full weight bearing was achieved at 20 weeks while only 2 (8%) patients required more than 20 weeks. 80% of cases required less than 16 weeks for union while 20% required more than 16 weeks. Average injury to surgery time was 3.62 days in the present series. Superficial stitch infection occurred in two cases. Deep infection occurred in a grade 2 compound fracture in a male who was treated initially with debridement and antibiotics. Conclusions: Good results are seen by distal femur locking condylar plate alone. It is the main implant of choice for distal femur fractures of all varieties. Best outcome is expected if fracture fixation is done following all the basic principles of fracture fixation. Advantage of the mechanical properties of a locking plate is definitely useful.